Acceptor doping effects on microstructure, thermal and electrical properties of proton-conducting BaCe0.5Zr0.3Ln0.2O3−δ (Ln = Yb, Gd, Sm, Nd, La or Y) ceramics for solid oxide fuel cell applications. (20th February 2016) - Lyagaeva, J.; Antonov, B.; Dunyushkina, L.; Kuimov, V.; Medvedev, D.; Demin, A.; Tsiakaras, P.
Highlights: BaCe0.5 Zr0.3 Ln0.2 O3−δ ceramics are prepared by citrate-nitrate combustion synthesis. Thermal expansion and TEC decrease with increasing ionic radius of Ln 3+ . The transport of materials at 600–900 °C is determined by grain conductivity. Y- and Yb-doped samples are characterized by highest total and ionic conductivity. Abstract: In the present work, six materials belonging to Ln-doped BaCeO3 –BaZrO3 system (Ln = Yb, Y, Gd, Sm, Nd, La) are prepared and characterized. The impact of the type of the acceptor dopant on i) the microstructure (relative density, size and grain morphology), ii) the thermal properties (linear expansion, thermal expansion coefficient) and iii) the electrical properties (nature and value of conductivity), is identified. The method of the modified citrate-nitrate combustion synthesis is adopted in order to achieve single-phase ceramic samples with relative density higher than 94% at reduced sintering regime (1450 °C for 5 h). It is found that: (i) the mean grain size grows (from 1.4 to 3.8 μm), (ii) the thermal expansion coefficient increases (from 7.6·10 −6 to 11.3·10 −6  K −1 in the high-temperature range), (iii) the ionic conductivity decreases (from 10.2 to 0.3 mS cm −1  at 800 °C) with increasing ionic radius of acceptor Ln-dopant. It is also found that BaCe0.5 Zr0.3 Y0.2 O3−δ electrolyte can be considered as the most optimal one for IT-SOFC applications from the view point of electrical properties. However, in the temperature interval of 550–700 °C, this sample possesses nonlinear thermal expansion.